Silica Gel Functionalized with 4-Amino-5-(4pyridyl)-4H-1,2,4-triazole-3-thiol and their Use as a Copper Sorbent and Electromediator for Voltammetric Detection of Ascorbic Acid - Magossi, Maiara de Souza [UNESP]; Maraldi, Vitor Alexandre [UNESP]; Magossi, Mariana de Souza [UNESP]; Dias Filho, Newton Luiz [UNESP]; Carmo, Devaney Ribeiro do [UNESP] (Wiley-Blackwell, 2018)
In this work, the 3-chloropropyl silica gel (SG) was prepared and organofunctionalized with 4-amino-5-(4pyridyl)-4H-1,2,4-triazole-3-thiol (SGA), that was characterized by infrared spectroscopy (FTIR) and cyclic voltammetry (CV). The cupric ions (Cu2+) sorption on the silica functionalized surface (CuSGA) were performed in aqueous solution, at room temperature. It was performed a systematic study about voltammetric behavior of CuSGA, where the cyclic voltammogram of graphite paste electrode modified with CuSGA exhibited a single redox pair with formal potential (E-theta ')=0.30 V assigned to the process Cu+/Cu2+, (KCl 1.0 mol L-1, v=20 mV s(-1)). The graphite paste electrode modified with CuSGA was sensitive to different concentrations of ascorbic acid and then an analytical curve could be constructed, with a linear response of 6.0x10(-6) to 9.0x10(-5) mol L-1 (R=0.9988) and a relative standard deviation of +/- 2.5 % (n=3). The detection limit (3 sigma) and amperometric sensitivity were 4.78x10(-6) mol L-1 and 115.96 mA/mol L-1, respectively.
Keywords: Silica gel; 4-amino-5-4(pyridyl)-4H-1,2,4-triazole-3-thiol; Cyclic voltammetry; Ascorbic acid